The Introduction to Python Programming Language for Students at Mtsn 4 Pandeglang School - M. BADRU TAMAM; masduki asbari (Journal of Community Service and Engagement, 2022)
The Industrial Era 4.0 brings Indonesians to a technological mindset that covers various aspects of life. Technology is now reopened to luxury things so that people cannot be separated from the rise of technological facilities. In preparation for entering the industrial era 5.0, there is no doubt that information retrieval is strongly supported and facilitated by various technology-based devices and applications. Information that is currently an important basic material in forming concrete data makes information important in various aspects of life. Based on the saying "don't know then don't love" will bring every human being will continue to need the information used to recognize something so that it can more quickly adapt and easily accept the positive things that exist. For this reason, there are computer-based applications made using certain programming language coding as a tool that can help humans in finding things that can be information for them. In response to this, where there are still many people who are not familiar with coding, especially school-age children, I intend to help one of the current government programs, namely helping programs that bring people more familiar with coding, especially at school age.